IDENTIFICATION OF POTENTIAL RIP CURRENT ON SEKUNYIT BEACH, SOUTH BENGKULU (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2022)
Rip current is one of the causes of beach accidents, dragging visitors off the coast. The purpose of this research was to determine the hydro-oceanographic characteristics of rip current generator and identification the potential zone of rip current at Sekunyit Beach, south Bengkulu., The method in this research is in situ measurement of the hydro-oceanographic parameters of the rip current generators and the zone mapping of the potential return currents through the visualization of aerial photos using of drone. Based on the results, it was shown that the potential zone of ​​frequent occurrence of rip current is southeast of the Sekunyit Beach in the west monsoon and the east monsoon. The surf type is plunging type, a steep beach morphology with a slope of 19°. The wave height and current speed are greater than other area with an average wave height of 0.38 m and current speed of 0.88 m/s. Therefore, visitors are expected to be more careful if in the southeast zone of Sekunyit Beach, so as to reduce the occurrence of beach accidents.